2019
DOI: 10.1016/j.biomaterials.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polymeric nanoparticles administered in the cerebrospinal fluid: Brain biodistribution, preferential internalization in microglia and implications for cell-selective drug release

Abstract: Cell-selective drug release Modulation of neuroinflammation in the central nervous system (CNS) holds great promise for the treatment of several neurodegenerative diseasesmany CNS disorders but it is still challenging. However, selective cell targeting remains challenging. We previously exploited demonstrated that polymeric nanoparticles (NPs) injected intra-parenchyma in the brain can be internalized specifically in to obtain cell specific uptake in microglia/macrophages surrounding the injection site, upon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…The size of nanoparticles influences biodistribution, and generally smaller nanoparticles penetrate the CNS faster and with higher specificity than larger ones (Mahmoud et al, 2020). In addition to CNS penetration, nanoparticle properties also have an impact on cell targeting (Peviani et al, 2019). For instance, ligand-free 4 nm polyamidoamine dendrimers selectively accumulate in activated microglia and astrocytes in a model of cerebral palsy (Dai et al, 2010).…”
Section: Nanoparticles For Drug Delivery To the Cnsmentioning
confidence: 99%
“…The size of nanoparticles influences biodistribution, and generally smaller nanoparticles penetrate the CNS faster and with higher specificity than larger ones (Mahmoud et al, 2020). In addition to CNS penetration, nanoparticle properties also have an impact on cell targeting (Peviani et al, 2019). For instance, ligand-free 4 nm polyamidoamine dendrimers selectively accumulate in activated microglia and astrocytes in a model of cerebral palsy (Dai et al, 2010).…”
Section: Nanoparticles For Drug Delivery To the Cnsmentioning
confidence: 99%
“…This is not surprising and is in line with what has been reported by other authors (where only partial co-localization between TSPO-targeted NPs and mitochondria was reported [ 9 , 30 ]). In previous studies, we reported that our polymeric NPs can be internalized in microglia cells even without surface functionalization, through the interaction with scavenger receptors that are highly expressed by microglia/macrophages [ 22 ]. Based on the results of the confocal analyses performed with 6PBR30, and since TSPO is mainly localized on mitochondria, it can be hypothesized that the 6PBR30 NPs (as most likely also other TSPO-ligand functionalized NPs), are retained on the mitochondria network through the interaction of TSPO after cellular internalization through other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the synthesis of zwitterionic biodegradable NPs whose properties can be readily modulated during the synthesis thus providing versatile platforms for the loading of poorly water-soluble drugs with minimal use of toxic organic solvents and providing enhanced stability to the formulation [17,20,21]. We showed that these NPs are able to be preferentially internalized in the microglia after administration into the spinal cord or in the cerebral lateral ventricles [20,22]. On the other hand, they were unable to differentiate between active and non-active microglia.…”
Section: Np Synthesis and Functionalization With The Tspo-ligandmentioning
confidence: 99%
“…Over the last 5 years, several contributions in the field (Elzoghby et al, 2016 ; Patel and Patel, 2017 ; Peviani et al, 2019 ; Birolini et al, 2021 ) highlighted that the size and surface charge of the NPs are critical features that must be controlled in order to achieve good NP biodistribution in the brain as well as selective cell targeting.…”
Section: Non-viral Methods For Gene Editing Applicationsmentioning
confidence: 99%